Telecommuting and the Demand for Urban Living: A Preliminary Look at White-collar Workers. - Gould Ellen, Ingrid; Hempstead, Katherine (Urban Studies (Routledge), 2002)
With recent advances in communications technology, telecommuting appears to be an increasingly viable option for many workers. For urban researchers, the key question is whether this growing ability to telecommute is altering residential location decisions and leading households to live in smaller, lower-density and more remote locations. Using the Work Schedules supplement from the 1997 Current Population Study, this paper explores this question. Specifically, it examines the prevalence of telecommuting, explores the relationship between telecommuting and the residential choices of white-collar workers and, finally, speculates about future impacts on residential patterns and urban form.